Improving Fine Motor Skills through Cutting and Sticking Activities with Colored Picture Media at RA Thoriqotun Najah Hadipolo Jekulo Kudus - Hindriani; Heni Apriani (MANDAILING GLOBAL EDUKASIA, 2025)
Improving Fine Motor Skills Through Cutting and Sticking Activities with Colored Picture Media in Group A Children of RA Thoriqotun Najah Hadipolo Jekulo Kudus in the 2020/2021 Academic Year. PKP. Semarang: PGPAUD BI, Semarang Open University. Learning videos from the Guru Pintar Online site